Avian Influenza A Virus (H5N1) Outbreaks, Kuwait, 2007 - Ahmad Al-Azemi; Justin Bahl; Sameer Al-Zenki; Yousif Al-Shayji; Sami Al-Amad; Honglin Chen; Yi Guan; J.S. Malik Peiris; Gavin J.D. Smith (Emerging Infectious Diseases, 2008)
Phylogenetic analysis of influenza A viruses (H5N1) isolated from Kuwait in 2007 show that (H5N1) sublineage clade 2.2 viruses continue to spread across Europe, Africa, and the Middle East. Virus isolates were most closely related to isolates from central Asia and were likely vectored by migratory birds.